TEACHER PERFORMANCE IS REVIEWED FROM MOTIVATION, COMPETENCE, DISCIPLINE AND WORK ENVIRONMENT (STUDY ON KINDERGARTEN TEACHERS IN PRAMBANAN SUB-DISTRICT) - Anggeani, Dewi; Sudarwati, Sudarwati; Istiatin, Istiatin; Mukti Aji, Lintang Pamugar (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
The purpose of this research is to identify the extent to which Kindergarten teachers in Prambanan District's motivation, competence, discipline, and work environment all have a role in shaping their students' academic and behavioral outcomes. Quantitative research methods are employed in this study. All 75 personnel from Prambanan District's kindergartens made up the study's population. This study used a census sampling method and collected data from 75 participants. Questionnaire-based information gathering. Statistical tests such the multiple linear regression test, the F test, the t test, and the coefficient of determination were utilized in the data analysis process. The study found that the performance of kindergarten instructors in the Prambanan District was highly influenced by four factors at the same time: teachers' motivation, teachers' competence, teachers' discipline, and the kindergartens' work environments. Based on the results of this research, kindergartens in the Prambanan District have begun implementing changes to boost agricultural extension employees' motivation, competence, discipline, and overall productivity in the workplace. Keywords: Teacher Performance, Motivation, Competence, Discipline, Work Environment